Efek imunomodulator saliva nyamuk Aedes aegypti (l.) Terhadap sistem imun manusia - Alya Arimbi Simangunsong; Mutiara Widawati (Loka Litbang Kesehatan Pangandaran, 2013)
Mosquito’s saliva is the main fundamental elements in the acquisition of human blood by mosquito, mosquito’s saliva inhibit blood hemostatic response, the influx of saliva also may stimulate the mechanism for effector formation of the host, also in this process we may find some microorganism transmission. By knowing on how the components of mosquito’s saliva process in stimulating our immune system, we could ensure the mechanism for pathogens and emerging diseases in our body. Flow Cytometry method used for detecting whether increased concentration of the saliva gland extract (SGE) affecting the proliferation and development of dendritic cells from bone marrow or not, while for the effect of SGE on lymphocytes is using colorimetric test. The concentration response curve was made to see the effect of SGE on Ae. aegypti cells (DC) and lymphocytes. The proliferation of DC from bone marrow precursor, its development and its function were not directly influenced by SGE of Ae. aegypti (concentration of 2.5 to 40μg/mL). While the results of SGE effects on lymphocytes showed that lymphocytes are extremely sensitive to saliva components. Based on the data, it was concluded that lymphocytes are potential to be a target for the main components of Ae. aegypti saliva compared to its dendritic cells